Influencing factors and nursing progress of intraoperative pressure injury (术中压力性损伤发生的影响因素及护理进展) - LI Dongyan (李冬燕) (Association of Integrative Nursing, 2022)
This article reviews the influencing factors of intraoperative pressure injury and the progress of preventive nursing. This paper provides reference and guidance to reduce the incidence of intraoperative pressure injury, improve patient comfort, reduce medical costs, and ensure patient nursing safety. (本文就术中压力性损伤发生的影响因素及预防护理进展进行了综述, 以期为降低术中压力性损伤的发生率、提高患者舒适度、降低医疗费用、保障患者护理安全提供参考和指导。)